Social Interactions and Modern Economic Growth (2018)
This paper offers a theoretical framework to understand the coevolution of social interactions and long-term economic growth. It begins by considering that most traditional societies did not have educational markets. Thus, access to the required knowledge for transiting to a modern economy had to be transmitted through social interactions, in particular, through the interaction between heterogeneous groups of people¿i.e. distant interactions. Once immersed in a modern economy, the productive system should have increased the demand for knowledge, promoting more distant interactions. Simultaneously, the emergence of distant interactions should have affected the connectivity of society, reducing its heterogeneity, making cheaper posterior interactions but reducing their profitability. Moreover, social interactions competed and benefited from other nonmarket activities, child rearing specifically. The model arrives at four basic predictions.